Strategy for Depicting the Character of Water in “Tabuh Kreasi Tirta Pemutih” - Mayura, I Putu Nanda Yoga; Ardini, Ni Wayan; Yudarta, I Gede (Journal of Aesthetics, Creativity and Art Management, 2025)
This study aims to provide a reference regarding the methods or techniques used by a Balinese Gamelan music composer in depicting a water character. Qualitative research is used because it is an appropriate type of research where the data obtained is a description of the condition of an object being studied. The data collection techniques used in this research are literature study, observation, interviews and documentation. There are several strategies that can be used to depict the character of water, which the composer previously used in the work “Tabuh Kreasi Tirta Pemutih”, such as processing the battens found in Balinese Gamelan as a medium for speaking, ornamenting the playing patterns of the instruments, and utilizing various song genres that can be played by Gamelan Semarandana. This study contributes to providing thoughts or points of view regarding strategies or techniques that can be used in depicting the character of water in a Balinese karawitan musical composition using gamelan as a medium for expression.